Pelatihan Pembawaan Cerita untuk Peserta Lomba Storytelling dalam Rangka Bulan Bahasa di SMK Negeri 3 Palembang - Muhammad Suardi; Emawati Emawati (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2025)
The storytelling training held during the Language Month at SMK Negeri 3 Palembang aimed to enhance students’ storytelling skills as competition participants. This program employed discussion and hands-on practice to train techniques such as intonation, facial expressions, and gestures relevant to story flow. The results showed significant improvements in participants’ confidence and communication skills. However, challenges such as tight school schedules and limited mentors were identified. Evaluation suggests better planning, extended training duration, and involving more mentors to improve future program effectiveness.